The Influence of Operating Profit and Loss and the Size of The Public Accounting Firm on Audit Delay - Fithri Dzikrayah; Silvia Septiani; Mia Lasmi Wardiyah; Mia Nurhasanah; Qheista Noor Fiddienillah (Tazkia Islamic University College, 2024)
This research aims to determine and analyze the influence of Operating Profit and Loss and the Size of the Public Accounting Firm (KAP) partially on Audit Delay. The influence of Operating Profit and Loss and Size of the Public Accounting Firm (KAP) simultaneously on Audit Delay in companies listed on IDX-MES BUMN 17 Period 2018-2022. This research uses a descriptive method with a quantitative approach. The statistical test tool uses the help of the IBM SPSS Statistics 27 version program. Operating Profit and Loss partially influence Audit Delay with a value of count 3,832 > table 2,018. The size of the Public Accounting Firm partially has no effect with a value of count -1.605 < table 2.018. Operating Profit and Loss and the Size of the Public Accounting Firm simultaneously influence Audit Delay with a value of Fcount 7.391 > Ftable 3.214. The R Square value obtained was 26.0%; the remaining 74.0% was influenced by other factors not examined in this research. Thus, the relationship between the variables in this study has a trim level of relationship. Companies should pay more attention to the timeliness of submitting financial reports, considering the importance of economic reports in decision-making. The manager evaluates the performance of each division to minimize delays in submitting financial reports. Future researchers can add independent variables and observation periods and expand the research object. Researchers want to know the extent to which these two variables play a role in influencing Audit Delay, especially in companies listed on IDX-MES BUMN 17, and can provide further information.